SOSIALISASI PAJAK BUMI BANGUNAN MEMODERASI PENGARUH PENGETAHUAN PAJAK MASYARAKAT TERHADAP KEPATUHAN PAJAK - Sherla Nursela; Verliani Dasmaran; Nani Sriyani (Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine tax knowledge in the Langen Sari village community and its effect on tax compliance, as well as the moderating role of tax socialization on land and building tax (PBB). The results of the study prove. Land and building taxes have an influence on regional development, especially in the infrastructure sector, but also public compliance in paying land and building taxes is still very low. The data used in this study is primary data collected through a questionnaire technique of 42 respondents, obtained from a population of 1,051. This research uses multiple regression analysis method and t test.